The lives of Reformers - Gilpin, William (T. Cadell and W. Davies, 1809)
I. The lives of John Wicliff, and of the most eminent of his disciples; Lord Cobham, John Huss, Jerome of Prague, and Zisca. Also the life of Hugh Latimer.--II. The lives of Thomas Cranmer, archbishop of Canterbury; and of Bernard Gilpin.